Technological adjustments in textile, clothes and leather industries: an alternative pathway for competitiveness - Marisa Cesario; Maria Teresa Noronha Vaz (European Regional Science Association (ERSA), 2010)
Labour-intensive industries, located in medium/high-cost areas are presently facing increasing low-cost competition and outsourcing with tremendous consequences at the regional employment level. The ability to react and technologically adjust to the challenges of this harder market conditions is what determines whether a region is a producer of high value-added goods or just a merely subcontractor. In fact, alternative employment opportunities may arise from complementary areas linked to technological innovations and although one can expect further job decline in manufacturing productive units, it is also expectable that more qualified jobs may be created in complementary areas, such as design, marketing, retail and management. The first objective of the present research is to characterise the process of adoption of new technologies in textile, clothes and leather (TCL) sectors from a group of Southern European regions, characterised by their economic vulnerability and dependence on these sectors. The results revealed that we are in the presence of a process: a) developed internally; b) supplier dominated and c) motivated by the international market. The second objective is to observe the impacts of technical change on local employment structures, namely regarding employment levels and skills. The results indicate that firms investing in new plant and equipment and firms investing in the development of new products are more likely to be increasing employment than the others. Also, firms hiring in these sectors, look for adequate qualifications, in particular regarding the ability to work with internet and marketing technology tools. We conclude that alternative pathways for competitiveness in these industries can be found through higher productivity levels driven from a much reduced workforce, if greater proportion of their turnover could be invested in technology and employment qualification.
Keywords: 330